Cutting temperature in rotary ultrasonic machining of titanium: experimental study using novel Fabry-Perot fiber optic sensors - Zou, Xiaotian; Cong, Weilong; Wu, Nan; Tian, Ye; Pei, Zhijian J.; Wang, Xingwei (My University, 2013)
Titanium has a wide variety of applications, particularly in the aerospace industry. However, because of its low thermal conductivity and high strength, machining of titanium is very difficult. The heat generated in machining can dramatically shorten the tool life. Rotary ultrasonic machining (RUM) is a non-traditional machining process, and has been used to machine various difficult-to-machine materials. Investigations have been reported regarding effects of machining variables (including ultrasonic power, tool rotation speed, and feedrate) on several output variables in RUM, such as cutting force, torque, surface roughness, edge chipping, material removal rate, and tool wear. However, there have been few studies on cutting temperatures in RUM. This paper presents an experimental study on cutting temperature in RUM of titanium. It is the first study to utilise fibre optic temperature sensors to measure the cutting temperature in RUM. The results revealed effects of machining variables on cutting temperature in RUM, and demonstrated that Fabry-Perot (FP) fibre optic sensors offer more accurate localised measurement of temperature in RUM than thermocouples.
Keywords: Rotary ultrasonic machining; Cutting temperature; Titanium; Fabry-Perot; Fiber optic sensor